Amor en clima frío - Mitford, Nancy, 1904-1973 (Libros del Asteroide, 2013)
Polly Hampton has long been groomed for the perfect marriage by her mother, the fearsome and ambitious Lady Montdore. But Polly, with her stunning good looks and impeccable connections, is bored by the monotony of her glittering debut season in London. Having just come from India, where her father served as Viceroy, she claims to have hoped that society in a colder climate would be less obsessed with love affairs. The apparently aloof and indifferent Polly has a long-held secret, however, one that leads to the shattering of her mother's dreams and her own disinheritance. When an elderly duke begins pursuing the disgraced Polly and a callow potential heir curries favor with her parents, nothing goes as expected, but in the end all find happiness in their own unconventional ways.